Adult play(fulness) and the art of stuff-mess-wonder: Creative playful learning with the Comicubes - Katriina Heljakka (University of Huddersfield Press, 2023)
This article focuses on the materiality of adult playfulness. The studies synthesized in the article explore creative playful learning at adult age that manifests in association with using simple paper technology in the co-creative context of workshops built on a triad of experiences-stuff-mess-wonder. The article demonstrates how creativity works with a physical tool based on cardboard cubes used for experimentation, ideation and co-construction-the Comicubes. Based on the summarized findings of four workshops, the article concludes how the Comicubes can be an accessible, sustainable and therefore valuable alternative to commercial construction systems and tools alike, by offering a basis for creative play and contributing to experiences related to stuff-mess-wonder.